專業標準本位中等技職教育師資職前教育課程規劃之探究 Professional Standard-based Curriculum Planning for Secondary Technical and Vocational Teacher Education Program - 許宛琪 Wan-Chi Hsu (National Changhua University of Education, 2015)
近年來，我國開始推動專業標準本位師資培育政策，透過研訂國家層級教師專業標準，統攝所有師資培育政策規劃，提升教師素質。本研究主要以我國國家層級高級職業學校教師專業標準為基礎，透過個別訪談及焦點團體座談方式，訪談不同中等技職教育師資利害關係人，探討實施專業標準本位中等技職教育師資職前教育課程 規劃，以提供教育行政主管機關及師資培育相關單位之參考。本文首先探討專業標準本位師資培育發展脈絡，分析其興起之背景與意涵；其次，探析國內教育部委託教育專業單位研訂之國家層級高級職業學校教師專業標準，以了解中等技職師資專業能力內涵要素；再者，從中等技職師資不同利害關係人反映的實務觀點，探究我 國未來落實專業標準本位中等技職師資職前教育課程規劃方向與實施策略；最後，根據研究探究歷程，提出本文之結語。 In recent years, Taiwan has started to promote the professional standard-based teacher education policy, and set national teacher professional standards to guide teacher education policy aiming at raising teacher quality. The main purpose of this study was to explore the professional teacher standards for secondary technical and vocational teacher education and through interviews and focus groups interviews with stakeholders to understand how the standards can be applied in the design of pre-service teacher education program. Results obtained from this study are expected to provide useful information to educational administration bodies and teacher preparation institutions. In this article, the authors first introduced the background of the professional standard-based teacher education; then analyzed the contents of national professional teacher standards for secondary technical and vocational education; thirdly, investigated the direction and the strategies of professional standard-based curriculum planning for secondary technical and vocational pre-service teacher education program from stakeholders' perspectives. Finally, based on the analysis of the study, the authors made a number of remarks in conclusion.